KAJIAN PENURUNAN PARIWISATA DI DATARAN TINGGI KERINCI, PROVINSI JAMBI - Martha Pratama; Muhammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Highlands Kerinci as a tourism icon Jambi province has a natural beauty and unique culture.But in its development, Highlands Kerinci as a tourist destination is not progressing even tends to decline.Tourist arrivals decline that occurred a slump Kerinci Highlands tourism sector as a the local economy sector.Based on this, the objective of this study is to examine what and why a decline in tourism in the Highlands Kerinci, Jambi Province.The approach in this study using a mixture or mixed method approach that combines quantitative and qualitative analysis. These results indicate that the tourism life cycle Highlands Kerinci based model Butler reached the stage of tourism decline that lasted from 2005 until today. Conditions downturn in tourism in the Highlands Kerinci so far have an impact on not growing hospitality business where the rate of occupancy of his not always full, there are only 6 homestay survive, the disappearance of the craft center, a restaurant that is that's it and souvenir shops also began to disappear.Based on the analysis of the causes of the decline of tourism, the decline in tourism in the Highlands Kerinci caused by 12 factors which have a high influence that the hygiene conditions, travel time, sanitation facilities, accommodation, sports facilities, roads, banking facilities, information and promotion, health facilities, electricity networks , community and government support, and network communications. Based on interview note that the decline in tourism that occurred due to the Concerned Citizens Festival Lake Kerinci (FMPDK) were first able to become a mainstay in attracting tourists at the present time is not the main attraction again and walk monotonous. On the other hand there is a different view, namely the fact that tourism actually Plateau Kerinci stagnant and FMPDK not carried out professionally, crowded visitors FMPDK because they dance alone, a collection of bureaucrats and people were mobilized. Regardless of the differences above, the general decline in tourism Highlands Kerinci based on interviews due to the monotony of tourist attraction developed, lack of facilities and infrastructure supporting tourism, management of tourist attraction unprofessional and tourism policies that are not targeted and unsustainable.